O discurso literário: memórias lusófonas - Padovani, Micheline Tacia de Brito (2021)
This thesis is part of the Text and Discourse Research Line in the oral and written modalities of the Postgraduate Studies Program in Portuguese at PUC/SP. Its theme is: The discourse and representation of the historical and social context in Lusophone literary works, which brings the hypothesis that Lusophone literatures involved in historical and social context reveal, through discourse and discursive memory, marks of culture and identity. Guided by this perception, we defined the following research question: How are discursive memory and multiculturalism related in Portuguesespeaking literature? The specific objectives are: 1) to verify the discursive memory and multiculturalism in Portuguese-speaking works in view of the Portuguese language; 2) identify and analyze Lusophone literary sequences present in the works that make up the corpus; 3) select and analyze Lusophone literary sequences present in the works that make up the corpus. As analysis categories, we selected: discursive formation, discursive memory, discursive identity and multiculturalism. As theoretical support, we have highlighted: Abdala Júnior (2007), Hernandez (2005), Pereira (2014) on cultural aspects and social aspects of the history of Angola, Mozambique, Brazil and Portugal. For Lusophony and Lusophone discourse: Bastos and Brito (2006, 2012), Brito and Hanna (2014), Cristovão (2008), Namburete (2006). With respect to Lusophone literature: Chaves (1999, 2003, 2005), Coutinho (2004), Ervedosa (1974), Fonseca (2003). For literary discourse: Maingueneau (1995, 2005, 2006, 2008, 2010). About discursive formation: Foucault (1969;2013), Maingueneau (2008, 2015), Pêcheux (1971;2011, 1997, 2009), Pêcheux and Fuchs (1993). Regarding memory and discursive memory: Candau (2019), Le Goff (1999;2014), Paveau (2015). As for discursive identity: Dubar (2009, 2013), García Canclini (2006), Hall (2003, 2006, 2011, 2016). And multiculturalism: Bauman (2013), Bhabha (2013), Lopes (2013). The corpus is composed of four Portuguese-speaking literary works, from which we selected excerpts for analysis, the research is descriptive and interpretive. The results show that discursive memory and multiculturalism bring a hybrid constitution